Research on the Multilayer Network of Relations of Western Agricultural Trade along the Belt and Road - Fengjie Xie; Xiaoxiao Yin; Ruifen Sun (Mathematics, 2022)
This paper defines the weighted super adjacency matrix based on the existing super adjacency matrix. This paper, for the first time, combines the trade network, competitive network, and complementary network to construct the trade multilayer network, and innovatively defines the interlayer connections. Based on this, we build trade multilayer networks for three major agricultural products in the western region along the “Belt and Road”. The paper then proposes analytical methods, including a classification algorithm for local network relations and a comparative analysis of trade development priorities based on the local network relations. The former is used to identify and categorize key trading countries and potential trading countries for western agricultural products along the “Belt and Road”. The latter is used to examine the western regions’ order of priority in developing trade relations with the classified countries. According to the findings, category I agricultural trade has 37 key trading countries among the “Belt and Road” countries. Their local network relationships are classified into six groups, and their trade development priorities are classified into four levels. There are 49 key trading countries in category II agricultural trade. Their local network relations can be classified into three groups, and their trade development priorities can be classified into two levels. There are 62 key trading countries in category IV agricultural trade. Their local network relationships are classified into six groups, and their trade development priorities are classified into four levels. Furthermore, only Chile is a potential trading partner in category I agricultural trade. Finally, this paper offers policy recommendations for the development of agricultural trade along the “Belt and Road” in the western region.